Polihidramnios en Paciente de 19 años de edad con embarazo de +/- 36 semanas de gestación - Santos Montolla, Cinthia (2018)
The amniotic fluid (LA) is a fluid that is found surrounding the fetus inside the ovular membranes in the uterine cavity during the time of its development, in the case of excessive reduction it is called oligohydramnios and the increase as polyhydramnios. The polyhydramnioos is an excessive accumulation of amniotic fluid, its presence promotes maternal and fetal complications in 50% to 60% idiopathic. There are 3 levels of severity for the diagnosis: ILA Mild: 18-25 ILA Moderate: 25-32 ILA Severe:> 32 The treatment is: Amniorreducción: It is used to get the evacuation deliquido and the inhibitors of the prostaglandins: with indomethacin, 25mg every 6 hours initially. The study of the present clinical case corresponded to the appearance of polydramnios in a 19-year-old patient with a pregnancy of 36 weeks. From the information obtained in the anamnesis, the characteristic symptom of the pathology (costal compression symptoms, respiratory distress, presentation dystocia - pelvic); the gestational age (36 weeks) and the amniotic fluid index (27.30cm), thus fulfilling the diagnostic criteria for moderate preterm polyhydramnios. The procedures that were performed in the patient were emergency Caesarean, Prophylaxis before surgery, with antibiotic, antithrombotic measures, immediate puerperium control. The therapeutic management to which the patient was subjected was based on indications from the Ministries of Public Health that are found in the clinical practice guidelines for the treatment of obstetric pathologies